2009
DOI: 10.1192/bjp.bp.108.054429
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of online computerised cognitive–behavioural therapy without support for depression in primary care: randomised trial

Abstract: BackgroundComputerised cognitive–behavioural therapy (CCBT) might offer a solution to the current undertreatment of depression.AimsTo determine the clinical effectiveness of online, unsupported CCBT for depression in primary care.MethodThree hundred and three people with depression were randomly allocated to one of three groups: Colour Your Life; treatment as usual (TAU) by a general practitioner; or Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
4
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(164 citation statements)
references
References 57 publications
5
141
4
11
Order By: Relevance
“…Some RCT studies reported their objective was to establish the efficacy of a computer-based, clinician-assisted, intervention for depression Perini, Titov, & Andrews, 2009;, others examined the efficacy of unsupported computer-based interventions de Graaf et al, 2009;Meyer et al, 2009;Spek, Cuijpers et al, 2007). Others still in examining efficacy included support which was other than therapeutic (Christensen, Griffiths, & Jorm, 2004;.…”
Section: Methodological Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some RCT studies reported their objective was to establish the efficacy of a computer-based, clinician-assisted, intervention for depression Perini, Titov, & Andrews, 2009;, others examined the efficacy of unsupported computer-based interventions de Graaf et al, 2009;Meyer et al, 2009;Spek, Cuijpers et al, 2007). Others still in examining efficacy included support which was other than therapeutic (Christensen, Griffiths, & Jorm, 2004;.…”
Section: Methodological Characteristicsmentioning
confidence: 99%
“…The Colour your Life program (3 RCTs) was initially developed for use with over 50-years population (Spek, Nyklicek et al, 2007) and later adapted for use with an adult population (18-65;de Graaf et al, 2009;Warmerdam, van Straten, Twisk, Riper, & Cuijpers, 2008). It consisted of sessions on psycho-education, cognitive restructuring, behavior change, and relapse prevention.…”
Section: Computer-based Psychological Treatments For Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Institute for Health and Care Excellence (NICE) guidelines recommend iCBT as a treatment option in the management of mild to moderate depression [16]. The majority of studies have focused on participants who present with mild to moderate symptom severity meaning the evidence base investigating how internet-delivered interventions impact on severe depression symptoms is less established [17].…”
Section: Internet-delivered Interventionsmentioning
confidence: 99%
“…Un ECC con tres brazos comparó un tratamiento computarizado de orientación cognitivo conductual administrado en línea llamado "Coloree su vida", el manejo usual de la depresión llevado a cabo por un médico general y ambos juntos no encontrándose diferencias signifi cativas a los seis meses entre estas tres posibilidades en relación a sintomatología depresiva y calidad de vida 15 ;sin embargo, los análisis costo efectividad favorecían al tratamiento cognitivo conductual solo 16 . Cinco ECC prueban el uso del teléfono en el tratamiento de la depresión.…”
Section: Depresiónunclassified